The Effect of Exercise Training During Pregnancy to Improve Maternal Vascular Health: Focus on Gestational Hypertensive Disorders - Witvrouwen, Isabel; Mannaerts, Dominique; Van Berendoncks, An M.; Jacquemyn, Yves; Van Craenenbroeck, Emeline M. (Frontiers in Physiology, 2020)
Hypertensive disorders of pregnancy, including gestational hypertension and pre-eclampsia, occur in up to 10% of pregnancies and are associated with increased life-long cardiovascular risk. Physical activity improves cardiovascular health in pregnancy and may lower the risk of developing hypertensive disorders of pregnancy. However, a minority of pregnant women comply with the recommended level of physical activity. Adequate knowledge on the physiological effects of exercise in healthy pregnancy could help to overcome potential barriers as pregnancy is a unique window of opportunity to improve health outcomes for both mother and child. In this mini review, we discuss structural and functional vascular adaptations during healthy and hypertensive pregnancies, we elaborate on the effects of exercise on the vasculature and review the safety and existing evidence of exercise training as preventive therapy for gestational hypertensive disorders.